Ecology of the Early Jurassic bivalve Harpax spinosus (J. SOWERBY, 1819) - Fürsich, Franz; Karapunar, Baran; Werner, Winfried; Nuetzel, Alexander (Neues Jahrbuch für Geologie und Paläontologie-Abhandlungen, 2020)
The plicatulid bivalve Harpax spinosus is a common element of Pliensbachian to Lower Toarcian benthic community relicts occurring preferredly in fine-grained siliciclastic and mixed carbonate-siliciclastic sediments. There is general agreement that the bivalve was a secondary soft substrate dweller, being cemented with its flat to slightly concave right valve to small shells and bioclasts during early stages of growth and turning into a free recliner during later growth stages. Disagreement exists with respect to the life orientation of the bivalve, whether as free recliner it rested with its convex left valve or with its slightly concave right valve on the substrate. The former growth position would have required the bivalve to flip over when turning into a free recliner. Moreover, most authors assume that the bivalve discarded its host substrate during its reclining stage. The analysis of approximately 1500 specimens from the Upper Pliensbachian Amaltheenton Formation of southern Germany and time-equivalent horizons of southern France and Portugal shows that the bivalve remained cemented to the host substrate throughout its life time, even when the latter no longer supported the shell. The bivalve most likely rested with its concave valve on the soft substrate. The radially protruding spines served to keep the commissure above the sediment-water interface, to stabilize the shell and to prevent the shell from sinking into the sediment (snow-shoe strategy). Differences in the size of individuals at the localities investigated are thought to reflect differences in the degree of environmental stress, most likely caused by fluctuations in the oxygen content of the bottom water masses or by increasing soupiness of the substrate.
CRIS-Team WoS Importer:2020-09-11